Optimization of Growth, Yield, and Quality of Edamame : Effect of Doses of NPK fertilizer and Plant Spacing - Erika Widhasari; Kacung Hariyono; Sigit Soeparjono (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Edamame production in Indonesia is approximately 3.5 tons/ha, which is higher than ordinary soybeans which have an average production of 1.7 ± 3.2 tons/ ha. One of the reasons for the low yield of edamame in Indonesia is due to sub-optimal cultivation techniques, including tillage, fertilization and the use of organic matter. So it is necessary to do research with the title about the effect of NPK fertilizer dosage and spacing on the growth, yield and quality of edamame soybeans. The experiment was arranged using a factorial Randomized Block Design (RBD) consisting of two factors and five replications, so there were 16 treatment combinations. The first factor is the spacing of plants and the second factor is the dose of NPK Bianglala fertilizer. The first factor is NPK Bianglala Fertilizer (P): P0 = NPK 350kg/ha (350,000 g: 125,000 plants = 3 g/plant which is according to PT.GMIT SOP as a control), P1 = NPK 250kg/ha (250,000 g: 125,000 plants = 2 g/plant), P2 = NPK 300kg/ha (300,000 g : 125,000 plants = 2.5 g/plant). The second factor is the spacing (J): J0 = 10 cm x 30 cm which is according to PT.GMIT SOP as a control), J1 = 20 cm x 20cm, J2 = 20 cm x 30 cm, J3 = 15 cm x 30 cm. The observed variables included plant height 7 WAP, number of leaves 7 MST, number of pods 1, number of pods 2, number of pods 3, total number of pods, number of productive branches, fresh weight of pods per bed, dry weight of pods per bed, protein content, fat content, sucrose content. The results showed that the combined treatment with NPK fertilizer and spacing was able to change each observed variable. However, the combination of NPK fertilizer and spacing gave a very significant change in all observed variables. The combination of NPK 3 g/plant and spacing of 20 x 30 cm gave the best changes in the observed parameters of growth and yield of edamame plants.